2018
DOI: 10.1001/jamanetworkopen.2018.6567
|View full text |Cite
|
Sign up to set email alerts
|

United States State-Level Variation in the Use of Neuraxial Analgesia During Labor for Pregnant Women

Abstract: Key Points Question Does the prevalence of neuraxial labor analgesia vary across US states? Findings In this population-based, cross-sectional analysis of 2 625 950 pregnant women who underwent labor, Maine had the lowest adjusted neuraxial analgesia prevalence (36.6%) and Nevada the highest (80.1%). The odds of receiving neuraxial analgesia were 1.5-fold higher if the same patient received neuraxial analgesia in a high-use vs a low-use state; and 5.4% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 37 publications
3
84
0
Order By: Relevance
“…Subjects assigned to the control arm were also more likely to utilize positioning (or changes in position) during the intervention (73.7 vs. 23.8%, p ¼ 0.002) and on average had a higher heart rate following the intervention than those assigned to the VR arm (86.8 vs. 76.3, p ¼ 0.01). Other secondary outcomes did not differ (►Table 3).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Subjects assigned to the control arm were also more likely to utilize positioning (or changes in position) during the intervention (73.7 vs. 23.8%, p ¼ 0.002) and on average had a higher heart rate following the intervention than those assigned to the VR arm (86.8 vs. 76.3, p ¼ 0.01). Other secondary outcomes did not differ (►Table 3).…”
Section: Resultsmentioning
confidence: 95%
“…2 The most recent data suggest that overall 73.1% of women will opt for neuraxial analgesia during labor, though there is significant variation by region. 3 While many women opt for pharmacologic or neuraxial analgesia pain relief, there is also significant interest by women in complementary and alternative medicine (CAM) methods for pain relief. One Australian study reported that 73% of their sample used at least one kind of complementary therapy during pregnancy, some of which were for pain relief in labor.…”
mentioning
confidence: 99%
“…The use of epidural analgesia for labor in the United States was 73.1% in 2015, and as high as 86% at an academic tertiary center. (3,4) Epidural analgesia has been deployed in Vietnam in the past decade, but the technique is not uniformly covered by Vietnamese health insurance and many women remain unaware of this option.…”
Section: Introductionmentioning
confidence: 99%
“…Neuraxial labor analgesia is widely used to reduce pain during childbirth, ranging from 37 to 80% in the US [75]. One such neuraxial labor analgesia technique is epidural anesthesia.…”
Section: Labor Analgesiamentioning
confidence: 99%